Hydrophilic sulfonic acid-functionalized micro-bead silica for dehydration of sorbitol to isosorbide. Issue 16 (2nd February 2016) - Shi, Jun; Shan, Yuhua; Tian, Yuan; Wan, Yu; Zheng, Yitian; Feng, Yangyang
Abstract : The large pore diameter and hydrophilic surface of SA-SiO2 -60.5 are beneficial to sorbitol adsorption and isosorbide desorption, and inhibit the deposition of coke. Abstract : Different (3-mercaptopropyl)trimethoxysilane (MPTS ) loadings of sulfonic acid-functionalized micro-bead silica (SA-SiO2 ) were prepared by silylation and oxidation, and characterized by elemental analysis, SEM, FT-IR, TGA, NH3 -TPD, BET N2 adsorption–desorption and 13 C NMR CP/MAS. The as-prepared SA-SiO2 showed strong hydrophilic nature and excellent catalytic performance for dehydration of sorbitol to isosorbide. The selectivity to isosorbide is obviously affected by theMPTS loading. Using SA-SiO2 as a solid catalyst with 60.5%MPTS loading, 100% sorbitol conversion and 84% yield of isosorbide are achieved at 120 °C for 10 h under vacuum. The catalyst was reused 10 times without noticeable loss of activity and selectivity.